Hemipenes in females of the mexican viviparous lizard Barisia imbricata (Squamata: Anguidae): an example of heterochrony in sexual development. Issue 5 (15th September 2015) - Martínez‐Torres, Martín; Rubio‐Morales, Beatriz; Piña‐Amado, José Juan; Luis, Juana
SUMMARY: The sexual development of saurians follows a similar pattern to that described for other amniotes. Changes in the timing or sequence of development events are known as heterochrony. We describe the pattern of sexual development in the viviparous Mexican lizard Barisia imbricata and report heterochrony in the regression of hemipenes in this lizard. We collected gestating females; some lizards were subjected to partial hysterectomy and the embryos were processed using routine histological technique to assess gonadal development; the remaining embryos were used to assess the development of hemipenes. Other pregnant females were kept in captivity in individual terraria until the time of delivery. All neonates were sexed by eversion of hemipenes and some of their body characteristics were recorded. Several neonates were sacrificed and processed to establish gonadal histology and the young of the remaining litters were maintained in captivity to observe the fate of the hemipenes in both sexes. Gonadal development began at embryonic stage 33 and the hemipenes were visible at the same stage. In the neonates, the ovary contained oogonias and ovarian follicles, whereas the testicles showed testicular cords. All neonates had hemipenes and sex could only be established through direct observation of the reproductive ducts and gonadal histology. The hemipenes regression in the females begins after approximately 7 months of postnatal development and concludes at about 15 months of age. We think that the delayed regression of the hemipenes reflects evolutionary differences among reptiles and may be an indication of a stage in the evolutionary process of this species.